Talking Bodies
XIII, 233 p. 3 illus.
Keywords: In this collection leading thinkers, writers, and activists offer their responses to the simple question “do I have a body, or am I my body?”. The essays engage with the array of meanings that our bodies have today, ranging from considerations of nineteenth-century discourses of bodily shame and otherness, through to arguing for a brand new corporeal vocabulary for the twenty-first century. Increasing numbers of people are choosing to modify their bodies, but as the essays in this volume show, this is far from being a new practice: over hundreds of years, it has evolved and accrued new meanings. This richly interdisciplinary volume maps a range of cultural anxieties about the body, resulting in a timely and compelling book that makes a vital contribution to today’s key debates about embodiment. .